Oncogenic Human Papillomavirus DNA Loads in Human Immunodeficiency Virus-Positive Women with High-Grade Cervical Lesions Are Strongly Elevated - Weissenborn, S. J. (American Society for Microbiology, 2003)
Human papillomavirus (HPV) DNA loads of six oncogenic HPV types were measured by real-time PCR in cervical scrapes of human immunodeficiency virus (HIV)-infected and uninfected women. In both groups, HPV loads increased with the grade of cervical disease. HIV infection did not affect HPV loads in low-grade lesions but was associated with significantly higher HPV loads in severe dysplasia; highest loads were found in advanced HIV disease. Our data reflect the aggressive course of HPV infection in HIV-positive women.